Increasing antimicrobial activity of some plant extracts against antibiotic resistant Staphylococcus aureus by using silver nanoparticles - Shahad E. Hamed; Ayyad W. Al Shahwany (World Journal of Experimental Biosciences, 2016)
This study was carried out to determine bacteriostatic property of green synthesized silver nanoparticles using Thymus vulgaris L., Zingiber officinale Roscoe and Cinnamomum zeylanicum phenolic plant extracts as reducing agent against multiple drug resistant (MDR) of six isolates of Staphylococcus aureus isolated from blood and wound. Several experiments were conducted to study the antibacterial effect of phenolic extracted from plants and combination of phenolic with silver nanoparticles by determining the minimum inhibitory concentrations (MICs). Also, the study included identification of active compounds present in the phenolic extracts by fast liquid chromatography (FLC). The study focused on the characterization and application of silver nanoparticles [Ag-NPs] which indicated a size range of 101.77 nm. The Complete Randomized Design [CRD] was used as an experimental design. Data were analyzed by using statistical analysis system- SAS to study the effect of different phenolic plant extracts and the nanoparticles on some bacterial isolates. All plant extracts showed high activity against all S. aureus isolates. Besides, the silver nanoparticles have potent antibacterial activities against all S. aureus isolates. The FLC results showed that T. vulgaris phenolic extract was the most effective against S. aureus isolates than the other tested extracts because of total concentration of the identified phenols was the highest in T. vulgaris extract (968.95 μg/ml). The data indicated that the lowest effective concentrations for T. vulgaris and nanoparticles were 6.25 and 3.125%. Analyses of the interaction data between T. vulgaris extract with silver nanoparticles showed the lowest effective concentrations were 12.5, and 3.125%, respectively. But in case of C. zeylanicum and Z. officinale were 100, 6.25% and 50, 6.25%, respectively. Finally, using plant extracts with silver nanoparticles as new types of bacteriostatic agent led to decrease concentration for both of them, which reduce their side effects on other living organisms.
Keywords: Multiple drug resistant, Phenolic plant extracts, Silver nanoparticles, Staphylococcus aureus.